Numerical methods - Sukhendu Dey (McGraw-Hill Education, 2013)
This book is a complete, unified, informative, lucid, and adequate for learning and using of numericalmethods for science students at undergraduate and postgraduate level. The book will also cater needsof engineering students in Numerical Methods.